Health-Related Quality of Life and its Association with Depression in Type II Diabetes Mellitus Patients: A Cross-Sectional Study from Delhi - Kanika Singh; Anita Shankar Acharya; Sanjeev Kumar Rasania; Jyoti Khandekar; Rodney Preetham Vaz (Indian Journal of Medical Specialities)
Background: Diabetes mellitus is noncommunicable disease that in most cases affects the whole life after diagnosis with long-standing effects and debilitating complications. It is also one of the top five causes of mortality and contributes significantly to morbidity. Besides limitations and complications to physical health, it also significantly affects the mental health and affects the quality of life (QOL) among the patients. The current study aimed at finding the QOL among the patients living with diabetes. Methodology: A cross-sectional study was conducted among diabetic patients attending a diabetic clinic at a district hospital in East Delhi between December 2016 and March 2018. A total of 250 study subjects were included in the study. The Physical Health Questionnaire (PHQ 9) and the World Health Organization QOL-BREF questionnaire were used along with a pretested, semi-structured questionnaire for data collection. Data analysis was done on SPSS 23. Results: The prevalence of depression was found to be 17.6% as per the PHQ-9. Health-related QOL was highest for social domain (63.81 ± 12.74) and lowest among the psychological domain (40.83 ± 8.93) followed by environment (46.92 ± 8.34). The score of all the domains was lowest among depressed group as compared to nondepressed study subjects. Conclusion: Mental health can be adversely affected in the case of patients with diabetes which in turn can affect the QOL of the cohort. Hence, it is important to focus on mental well-being of the diabetics and timely intervention.